2007
DOI: 10.1074/mcp.m600347-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Full Versus Partial Metabolic Labeling for Quantitative Proteomics Analysis in Arabidopsis thaliana

Abstract: In recent years a variety of quantitative proteomics techniques have been developed, allowing characterization of changes in protein abundance in a variety of organisms under various biological conditions. Because it allows excellent control for error at all steps in sample preparation and analysis, full metabolic labeling using Overall full metabolic labeling and partial metabolic labeling prove to be comparable with respect to dynamic range, accuracy, and reproducibility, although partial metabolic labeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 31 publications
3
121
0
Order By: Relevance
“…Three of these were also identified in a study of the Arabidopsis tonoplast (Shimaoka et al, 2004). In another proteomics study, Huttlin et al (2007) identified peptides for ESM1 in the organellar fraction but other putative MyAPs in both the organellar and microsomal fractions.…”
Section: Cloning and Identification Of Mvp1 As A Myapmentioning
confidence: 94%
See 1 more Smart Citation
“…Three of these were also identified in a study of the Arabidopsis tonoplast (Shimaoka et al, 2004). In another proteomics study, Huttlin et al (2007) identified peptides for ESM1 in the organellar fraction but other putative MyAPs in both the organellar and microsomal fractions.…”
Section: Cloning and Identification Of Mvp1 As A Myapmentioning
confidence: 94%
“…The MyAPs feature GDSLlike lipase motifs, but no lipase activity has yet been definitively established for any of the MyAPs. A number of proteomic studies have detected ESM1 in the vacuole (Carter et al, 2004;Shimaoka et al, 2004;Huttlin et al, 2007). Five other putative MyAPs were detected in vacuoles (Carter et al, 2004).…”
Section: Cloning and Identification Of Mvp1 As A Myapmentioning
confidence: 99%
“…Experimental data points are shown as closed circles, and the least-squares fits using eqs [13][14][15][16][17][18][19][20][21][22] Composite peaks from unlabeled and fractionally 13 C-Ile-labeled peptides resulting from pulse labeling. Experimental data points are shown as closed circles, and the least-squares fits using eqs [13][14][15][16][17][18][19][20][21][22] Composite peak from an unlabeled and fractional 13 C-Ile/ 2 H-Leu-labeled peptide resulting from pulse labeling. Experimental data points are shown as closed circles, and the least-squares fits using eqs 13-22 are shown as the solid line.…”
Section: Discussionmentioning
confidence: 99%
“…There is one isotope envelope from the unlabeled species present at the beginning of the 15 N-pulse, and a second 15 N-enriched isotope envelope from the species biosynthesized after the pulse. The observed spectrum can be expressed as the sum of the two isotope distributions for the two species (14) where B is a baseline offset, A U is the amplitude of the unlabeled distribution S U (m), and A L is the amplitude of the labeled distribution S L (m). The isotope distributions for the unlabeled and labeled species are readily calculated in the μ-domain: (15) ( 16) In order to calculate the labeled distribution, a new atom type, N* for 15 N-enriched atoms, is introduced for the labeled nitrogen atoms, and n elements is increased by one.…”
Section: Analytical Description Of a Composite Unlabeled And Fractionmentioning
confidence: 99%
“…However, it works well for mammalian cell lines [113][114][115], but not so effective in autotrophic organisms such as cyanobacteria due to their ability to synthesize all amino acids [116,117]. The second primary method in stable isotope metabolic labeling relies on the introduction of a heavy isotope such as 15 N, often in the form of Na 15 NO 3 or K 15 NO 3 as a nitrogen source, is a powerful tool for the quantitative analysis in plant and bacteria [118,119]. Quantitative proteomics based on "metabolic labeling" has already been successfully used in some cyanobacterial strains [120][121][122].…”
Section: Challenge and Perspective In Ptm Proteomics Of Cyanobacteriamentioning
confidence: 99%